Percentiles for Height and Weight of Children between 6-14 Years of Age in Bandung - Hendra Permadhi; Doerjat Danoemoelja; Hartaman Tjokrohusada; Sugiri Sugiri (Paediatrica Indonesiana, 1976)
From a cross sectional study on height and weight of children from 6 to 14 years of age, percentile curves were drawn. This study was done in Bandung during a period of 10 months in 1973. The subjects were obtained from 215 elementary schools and 17 Kindergartens and 65,809 pupils were measured. Only 15,099 children were selected for this study based on their birthdates. The 1Oth, 30th, 50th, 70th and 90th percentiles, mean and standard deviations were calculated and plotted in graphs. Data within the range + and - 2 SD were considered normal. Data in the category between + 2 SD and 90th percentile were considered "Tall or heavy", between 30th and 70th percentiles "Average" and between 10th percentile and -2 SD "Short or light". Data outside the limits of -+- 2 SD were considered extremes. These graphs can be recommended in following the growth of children transversally as well as longitudinally.